A dashboard-based approach to measuring road freight transport performance in a food distribution company - Mar Vazquez-Noguerol; Jesús García-Arca; J. Carlos Prado-Prado (WPOM : Working Papers on Operations Management)
The optimization of road freight transportation, particularly within the context of food distribution companies, is imperative for enhancing operational competitiveness. This study emphasizes the significance of performance measurement through key performance indicators (KPIs) as a fundamental step towards enhancing operational efficiency. The objective of this empirical research is to furnish a comprehensive framework and methodology for implementing a performance measurement system that is specifically tailored to road freight transportation. Based on an action research approach, researchers collaborated closely with industry professionals, conducting a detailed case study in a food distribution company. The study identifies and defines critical indicators in areas such as arrival control at destinations, temperature monitoring at the start and end of trips, incident management, vehicle utilization, and productivity. This research makes significant contributions to the field, namely through the formulation of a guide for system implementation, the identification of usual challenges, and the presentation of best practices and recommendations to ensure successful system replication. The developed dashboard is characterized by its comprehensive customizability, with visualizations that are meticulously adapted to the specific requirements of stakeholders. This functionality empowers the effective training and engagement of relevant personnel, thereby fostering a collaborative and informed environment.